You can solve 3 equations having 3 variables. Here are the 3 equation examples: x+2y+z=10. 2x-y+3z=-5. 2x-3y-5z=27. The goal is to reduce to 2 equations having 2 variables. Multiply bottom equation by (-1). Rewrite 2nd and 3rd equation. 2x-y+3z=-5. Add -2x+3y+5z+-27. Equals 2y+8z=-32. Go back to original equations and multiply by (-2). Then you have -2x -4-2z=-20. plus 2x -y +3z. When you add these 2 equations, the answer is -5y +z = -25. You have now reduced the equations from 3 equations down to 2 equations having 2 variables.